2008
DOI: 10.1007/s10856-008-3626-8
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization of biopolyurethanes based on cellulose derivatives

Abstract: Surface tension parameters and surface morphology of biopolyurethanes based on cellulose derivatives thin films, before and after HF cold plasma treatment has been investigated. Calculations are based on the geometric mean approach of Owens and Wendt, Rabel and Kälble, on the Lifshitz-van der Waals acid/base approach of van Oss and co-workers and on the theoretical methods involving quantitative structure-property relationship. For all the investigated samples the polar component contributes significantly to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…[16] The total SFE and the components were calculated using the acid/base (LW/AB) approach of van oss and good (Equation (3)) [17] which divides the total SFE into dispersive Lifshitz-van der Waals interaction ( (Table 1). [18][19][20] Subscripts 'lv' and 'sv' denote the interfacial liquid-vapor and surface-vapor tensions, respectively, TOT sv . Blood compatibility is dictated by the manner in which their surfaces interact with blood constituents, like red blood cells and platelets.…”
Section: Contact Angle and Surface Free Energymentioning
confidence: 99%
“…[16] The total SFE and the components were calculated using the acid/base (LW/AB) approach of van oss and good (Equation (3)) [17] which divides the total SFE into dispersive Lifshitz-van der Waals interaction ( (Table 1). [18][19][20] Subscripts 'lv' and 'sv' denote the interfacial liquid-vapor and surface-vapor tensions, respectively, TOT sv . Blood compatibility is dictated by the manner in which their surfaces interact with blood constituents, like red blood cells and platelets.…”
Section: Contact Angle and Surface Free Energymentioning
confidence: 99%
“…Among the PPG-HPC, PTHF-HPC and PEA-HPC samples the most promising thromboresistant ones are PTHF-HPC and PEA-HPC. In our previous paper, the fibrinogen adsorption tests, (Macocinschi et al, 2009a), revealed that PTHF-HPC and PEA-HPC polyurethanes proved to be indicated for thromboresistant devices, and the polyether-urethane PTHF-HPC proved to have more relevant haemocompatible material qualities. From literature for Biospan polyurethane, (Korematsu et al, 1999), the values for adhered thrombocytes found are 101500 adhered thrombocytes per mm 2 .…”
Section: Platelet Adhesionmentioning
confidence: 97%
“…Polyester-and polyether-urethanes have been modified with hydroxypropyl cellulose aiming the change of their surface and bulk characteristics to confer them biomaterial qualities Macocinschi et al, 2009a;Macocinschi et al, 2009b). In this respect, dynamic contact angle measurements, dynamic mechanical analyses accompanied by mechanical testing have been done.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Polyester-and polyether-urethanes have been modified [11][12][13], with hydroxypropyl cellulose to improve their surface characteristics and to generate biomaterial qualities. Platelet adhesion test has been carried out in vitro and it was found that the cellulose component in the polyurethane matrix reduces the platelet adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…For estimation of the haemocompatibility properties of the obtained materials, water sorption was determined as well as the amount of fibrinogen adsorbed from solution, the amount of fibrinogen adsorbed from blood plasma, and the time of prothrombin consumption [12].…”
Section: Introductionmentioning
confidence: 99%